Activation of 5'AMP-activated protein kinase in skeletal muscle by exercise and phytochemicals - Tatsuro Egawa; Satoshi Tsuda; Rieko Oshima; Katsumasa Goto; Tatsuya Hayashi (Japanese Society of Physical Fitness and Sports Medicine, 2014)
Skeletal muscle is the principal site of whole-body glucose, lipid, and energy metabolism, and several adaptive responses to physical exercise (muscle-contracting stimuli) by skeletal muscle contribute to whole-body health-promoting effects. Acute and/or repeated activation of skeletal muscle 5'AMP-activated protein kinase (AMPK) by physical exercise controls several metabolic adaptations. Thus, skeletal muscle AMPK is likely to be a "central molecule" that mediates anti-obesity/antidiabetes effects in response to physical exercise. Meanwhile, recent reports suggest that functional foods and their natural components (so-called phytochemicals) have anti-obesity/antidiabetes properties that stimulate skeletal muscle AMPK activity in a similar manner to physical exercise. For example, caffeine is a plant alkaloid that activates skeletal muscle AMPK and the activation mechanisms are exercise-like in terms of the association between α isoform-specific AMPK activation and the energy status. Furthermore, berberine, a component of natural medicines, resveratrol, a polyphenol found in red wine and other plant products, and caffeic acid, a coffee polyphenol, all stimulate AMPK activation in skeletal muscle accompanied by energy deprivation. In this study, we review our recent findings and related studies of the activation of AMPK by physical exercise and phytochemicals.